2010
DOI: 10.1017/s1368980010002375
|View full text |Cite
|
Sign up to set email alerts
|

To what extent have sweetened beverages contributed to the obesity epidemic?

Abstract: Objective: A systematic literature review was conducted to determine whether sweetened beverage intake increases the risk for obesity, and the extent to which it has contributed to recent increases in energy intake and adiposity in the USA. Design: The search included studies published between 1970 and 2010 that examined secular trends, mechanisms, observational associations and intervention outcomes. Observational and intervention studies were abstracted and systematically evaluated for quality. Setting: Tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
2
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 103 publications
6
134
2
8
Order By: Relevance
“…The list of studies within each review is presented in Supplementary Tables 3-5 (see online supplementary material at http://www.liebertpub .com). All reviews concluding that there was a direct association between SSB intake and weight gain, overweight, and obesity in children and adolescents included longitudinal studies, eight included intervention studies, 18,26,27,[29][30][31][32]34 and four included cross-sectional studies as well. 26,29,31,34 Among the four reviews that did not find a direct association between SSB intake and weight gain, overweight, and obesity in children and adolescents, all included intervention studies, 14,25,33,35 two further included longitudinal studies, 25,35 and one also included cross-sectional studies 25 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of studies within each review is presented in Supplementary Tables 3-5 (see online supplementary material at http://www.liebertpub .com). All reviews concluding that there was a direct association between SSB intake and weight gain, overweight, and obesity in children and adolescents included longitudinal studies, eight included intervention studies, 18,26,27,[29][30][31][32]34 and four included cross-sectional studies as well. 26,29,31,34 Among the four reviews that did not find a direct association between SSB intake and weight gain, overweight, and obesity in children and adolescents, all included intervention studies, 14,25,33,35 two further included longitudinal studies, 25,35 and one also included cross-sectional studies 25 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Five reviews 14,18,27,28,31 did not state their source of funding, six 26,29,30,[32][33][34] were publicly funded, and two 25,35 were funded by the industry. Conflict of interest was not reported in six reviews, 18,25,28,29,31,34 authors of five reviews 26,27,30,32,35 reported not having any conflict of interest, and authors of two reviews 14,33 reported having conflict of interest (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…18 SSB intake is associated with dental caries, increased energy intake, overweight, obesity, and is an independent risk factor for diabetes and heart disease. [18][19][20][21][22] Health effect studies on energy drinks find caffeine consumption by youth associated with cardiac abnormalities, caffeine toxicity, and diabetes. 15,17 …”
Section: Consumptionmentioning
confidence: 99%
“…3,18 To induce sales and impulse purchases, retail establishments use price discounts and locate products in check-out aisles, in 'special displays', and at the end of aisles. 23,24 The price of SSBs has not kept up with inflation, for decades remaining consistently below the consumer price index.…”
Section: Retail Environmentmentioning
confidence: 99%
“…Although consumption of SSB is not the only cause of obesity, it is strongly linked to increased energy intake (11) and weight gain in both adults and children due to the high sugar content in these drinks. A 330 ml can of carbonated soft drink in South Africa contains an average of 40 g of sugar and the same size of sweetened fruit juice approximately 45 g of sugar.…”
mentioning
confidence: 99%